2019
DOI: 10.1073/pnas.1817588116
|View full text |Cite
|
Sign up to set email alerts
|

Ingroup vigilance in collectivistic cultures

Abstract: Collectivistic cultures have been characterized as having harmonious, cooperative ingroup relationships. However, we find evidence that people in collectivistic cultures are more vigilant toward ingroup members, mindful of their possible unethical intentions. Study 1 found that Chinese participants were more vigilant than Americans in within-group competitions, anticipating more unethical behaviors from their peers. Study 2 replicated this finding by comparing areas within China, finding that people from China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 57 publications
11
92
0
Order By: Relevance
“…First, collectivistic culture promotes interdependence within the team, resulting in lower psychological safety. Under conditions of high team collectivism, interpersonal relationships are a key mechanism through which individuals become attached to workgroups; team members are more concerned about the appearance of risky interpersonal exchanges and more vigilant regarding interpersonal tensions [68]. In a highly collectivistic culture, employees devote more attention to contextual signs for building or maintaining relationships, meaning that guanxi HRM practice will be more operational for them, thus the perceived uncertainty and vulnerability in dealing with others on the team will deteriorate the negative effect of guanxi HRM practice on psychological safety.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…First, collectivistic culture promotes interdependence within the team, resulting in lower psychological safety. Under conditions of high team collectivism, interpersonal relationships are a key mechanism through which individuals become attached to workgroups; team members are more concerned about the appearance of risky interpersonal exchanges and more vigilant regarding interpersonal tensions [68]. In a highly collectivistic culture, employees devote more attention to contextual signs for building or maintaining relationships, meaning that guanxi HRM practice will be more operational for them, thus the perceived uncertainty and vulnerability in dealing with others on the team will deteriorate the negative effect of guanxi HRM practice on psychological safety.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…While individualism and collectivism are two distinct cultural values [21], the pathogen prevalence hypothesis holds that collectivism is more likely to promote protection against epidemics than does individualism [22,23]. Collectivism places more emphasis on in-group vigilance [24][25][26]. Such may contribute to people's intention to prevent COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…According to Markus and Kitayama (1991) , people from individualistic cultures tend to perceive themselves as autonomous and independent from others (an independent self-construal), making them likely focus on uniqueness and self-interest; in contrast, people from collectivistic cultures define themselves as connected and interdependent with others (an interdependent self-construal), making them likely emphasize social harmony and others’ feeling and attitudes ( Markus and Kitayama, 1991 ). In addition, although collectivist culture emphasizes harmony and cooperation, it has been found that people in collectivist culture are more alert to group members than those in individualistic culture ( Liu et al, 2019 ). Moreover, it has been suggested that both the independent and interdependent self-construals exist in all cultures ( Singelis, 1994 ; Oyserman et al, 2002 ; Sui et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%